Kuat Tekan Beton Blended Abu Terbang Dengan Tambahan Serat Nanas - Mohd. Rizki Novianto; Monita Olivia; Gunawan Wibisono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Blended fly ash concrete is concrete with partial cement substitution using pozzolan in the form of fly ash. This study examines the effect of adding pineapple fiber by 0%, 0.3%, and 0.6% of the concrete volume to the compression strength of blended fly ash concrete. Fly ash substitution in the concrete mixture was 10%. There were nine cylinder samples with size of 105 x 210 mm. Test were carried out after 28 days of immersed curing. All the pineapple fiber blended fly ash concretes have an increase in compressive strength at the age of 28 days. The maximum compressive strength was obtained on the blended fly ash concrete after adding pineapple fiber by 0.3%, with compressive strength value by 23.30 MPa., it was higher 27.042% than the 0% variation concrete (control). Based on all the test results, it can be concluded that the addition of pineapple fiber and the use of fly ash as a cement substitute in concrete has a positive impact on the compression strength of the concrete. Keywords: blended fly ash, fly ash, Portland cement, pineapple fiber, fiber concrete